Quantitative analysis of amoxicillin, its major metabolites and ampicillin in eggs by liquid chromatography combined with electrospray ionization tandem mass spectrometry. (1st February 2016) - Sun, Lirui; Jia, Longfei; Xie, Xing; Xie, Kaizhou; Wang, Jianfeng; Liu, Jianyu; Cui, Lulu; Zhang, Genxi; Dai, Guojun; Wang, Jinyu
Highlights: We describe a LC–MS/MS assay of amoxicillin, its metabolites and ampicillin in eggs. The method is in compliance with Decision 2002/657/EC and FDA guidelines. The method shows significant reduction in sample treatment time. The newly-developed method was successfully applied in real samples. Abstract: In this present study, we developed a simple, rapid and specific method for the quantitative analysis of the contents of amoxicillin (AMO), AMO metabolites and ampicillin (AMP) in eggs. This method uses a simple liquid–liquid extraction with acetonitrile followed by liquid chromatography–tandem mass spectrometry (LC–MS/MS). The optimized method has been validated according to requirements defined by the European Union and Food and Drug Administration. Extraction recoveries of the target compounds from the egg at 5, 10 and 25 μg/kg were all higher than 80%, with relative standard deviations not exceeding 10.00%. The limits of quantification in eggs were below the maximum residue limits (MRLs). The decision limits (CCα ) ranged between 11.1 and 11.5 μg/kg, while detection capabilities (CCβ ) from 12.1 to 13.0 μg/kg. These values were very close to the corresponding MRLs. Finally, the new approach was successfully verified for the quantitative determination of these analytes in 40 commercial eggs from local supermarkets.